Deformation analysis of double wall brazed tube in the multi-pass roll forming: Cross-sectional variation, stress-strain evolution and roundness assessment. (6th January 2023) - Liu, Mengmeng; Liu, Yuli; Li, Heng
Abstract: The deformation behavior of double wall brazed tube (DWBT) in the multi-pass roll forming (MPRF) process has an important impact on the forming accuracy. Thus, the reliable 3D finite element model of the MPRF process for DWBT was established considering the anisotropic Hill'48 yield criterion, then the deformation behavior of cross section from BHG2 steel strip to double wall tube (DWT) was analyzed. The results show that: (1) For cross-sectional variation of DWBT, 90° arm and circular arc are firstly formed asymmetrically on both sides, then the nodes close to circular arc move forward spirally to form inner tube. Afterwards, the composite structure including single wall and double wall appears with the MPRF forming. Finally, the nodes near 90° arm translate or rotate to shape outer tube. (2) Compared with the equivalent stress, the equivalent strain is regular and presents the characteristics of low in the middle and high on both sides in the transversal direction. Meanwhile, the transversal stress and strain are critical to the cross-sectional variation, and the sizing forming can homogenize the transversal strain and wall thickness. (3) The wall thickness from BHG2 steel strip to DWT has not changed significantly in the MPRF process. Additionally, the curvature of circular arc reduces first and then raises with the roll forming, and the smooth transition of the curvature is conducive to the close stick of the inner tube and outer tube. (4) In 720° curling forming, the formed circular arcs for inter wall have good roundness, whereas the outer wall is not fully formed at the end. After sizing forming, the outer tube deviates from the standard circle to a small extent in comparison with the inner tube.